2012
DOI: 10.1007/s11096-012-9731-2
|View full text |Cite
|
Sign up to set email alerts
|

Patients with advanced lung cancer: is there scope to discontinue inappropriate medication?

Abstract: The nal publication is available at Springer via http://dx.doi.org/10.1007/s11096-012-9731-2.Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…The literature search identified numerous, high-impact publications describing the incidence of polypharmacy and the proportion of geriatric patients prescribed PIMs [10,15,17,[19][20][21]; however, in cancer patients, there are only three retrospective and cross-sectional, small-scale trials [1,13,14]. In these trials, there was a lack of consensus guidelines for assessing PIMs, instead using the authors, or a medical officer's clinical opinion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature search identified numerous, high-impact publications describing the incidence of polypharmacy and the proportion of geriatric patients prescribed PIMs [10,15,17,[19][20][21]; however, in cancer patients, there are only three retrospective and cross-sectional, small-scale trials [1,13,14]. In these trials, there was a lack of consensus guidelines for assessing PIMs, instead using the authors, or a medical officer's clinical opinion.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of participants could contribute to the inconsistent results between the cancer trials; for example, Reichelmann et al found 22 % of patients with at least one PIM [13], compared to the 95 % found by Todd et al [14]. The study design may have also contributed to these results, as there was a lack of a clear, standardized algorithm or guideline used for the identification of PIMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of this decline occurs in the 6–12 months prior to death and is most likely the result of efforts to reduce the treatment burden in patients with terminal cancer 3. However, the possibility that some of this decline may be due to the development of contraindications to aspirin use in patients with metastatic disease should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of perimortality medication use in patients with cancer suggest that as many as a third of those who die from their cancer continue to receive medications for long-term cardiovascular disease prevention up to the time of their death 3. However, these studies have focused primarily on statin prescribing and have provided limited information on the prevalence of other cardiovascular medication use in the time close to death.…”
Section: Introductionmentioning
confidence: 99%